An integrative Whole Building Life Cycle Assessment (WBLCA) framework: A survey of software developers' perspective. (September 2022) - Sartori, Thais; Drogemuller, Robin; Omrani, Sara; Lamari, Fiona
Abstract: Whole Building Life Cycle Assessment (WBLCA) is an effective way of evaluating the environmental impact of a building's systems and materials. Designers usually rely on software tools to evaluate a building's environmental performance, and the barriers to the smooth use of these tools during design are extensive. Given the critical role software tools are playing in design practice, this research sought the opinions of WBLCA software tool developers to create a framework that better integrates WBLCA into the Building Project Process (BPP). A questionnaire of software attributes in each stage of BPP and the challenges associated with incorporating WBLCA into the BPP was followed by interviews to establish a greater understanding of the software tool developers' responses. The integrative framework illustrates the character of the WBLCA in each stage of BPP, including the goal of the assessment, the relevant software attributes, the applicable databases, and the primary stakeholders engaged in the process. For instance, design-oriented software attributes are more relevant in the early stages, and, as the BPP progresses, the assessment requires more transparency in the assumptions and outcomes. The findings from this study will guide software developers and policymakers to develop tools and procedures more aligned with designers interests. Highlights: Sustainability software capabilities define the design process. The sustainable design process moves from qualitative to quantitative metrics. The key decision for LCA building design does not match certification requirements. In-use results need to feed into the early stages of future projects.